MyMAP: World’s First Holistic Rating System for Motorcycles - Zulkipli, Z.H.; Alias, N.K.; Omar, A.; Kak, D-W.; Abdul Khalid, M.S.; Amir, A.S.; Mahmud, M.N.; Jawi, Z.M.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
MyMAP is the first of its kind and aims to stimulate healthy competition among motorcycle manufacturers towards safer designs, as well as to give the public more information when considering purchasing a motorcycle. MyMAP is additionally unique to other initiatives in the field as it introduces assessment criteria for the manufacturer’s effort towards educating and supporting the buyer on safe riding practices. This paper will discuss the vision, strategies, and challenges faced in establishing the program.